2019
DOI: 10.19173/irrodl.v20i1.3892
|View full text |Cite
|
Sign up to set email alerts
|

On the Efficacy of Open Educational Resources

Abstract: Open educational resources (OER), which are free and openly licensed educational materials, have been a widely discussed topic in response to high textbook costs, the need for more pedagogical flexibility, and inequality in access to educational materials. In this study we examine the efficacy of OER through a quantitative analysis of the impact of OER on student final exam performance in a large calculus course. Our dataset affords us a relatively large sample size, allows us to classify students in both trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Research topics include OER's impact on student enrollment (Grewe & Davis 2017), faculty perceptions (Jung, Bauer, & Heaps 2017), teaching practices (Lane & McAndrew 2010), public engagement (Scanlon 2014), funding policies (Stacey 2013), classroom ecology (Blyth 2014), institutional culture (Cox & Trotter 2016), multicultural competence (Lin & Wang 2018), and digital proficiency (Ramirez-Montoya, Mena, & Rodriguez-Arroyo 2017), to name but a few. Although a limited number of these studies negatively correlate OER with student performance (Gurung 2017; Robinson 2015), while others yield mixed results (Delgado et al 2019) or inconclusive findings (Griggs & Jackson 2017), the overwhelming consensus of OER research reveals consistently high levels of academic quality and efficacy.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Research topics include OER's impact on student enrollment (Grewe & Davis 2017), faculty perceptions (Jung, Bauer, & Heaps 2017), teaching practices (Lane & McAndrew 2010), public engagement (Scanlon 2014), funding policies (Stacey 2013), classroom ecology (Blyth 2014), institutional culture (Cox & Trotter 2016), multicultural competence (Lin & Wang 2018), and digital proficiency (Ramirez-Montoya, Mena, & Rodriguez-Arroyo 2017), to name but a few. Although a limited number of these studies negatively correlate OER with student performance (Gurung 2017; Robinson 2015), while others yield mixed results (Delgado et al 2019) or inconclusive findings (Griggs & Jackson 2017), the overwhelming consensus of OER research reveals consistently high levels of academic quality and efficacy.…”
Section: Literaturementioning
confidence: 99%
“…Despite OER's ability to reduce current price barriers to higher education (Hodgkinson-Williams & Arinto 2017), very little research to date has explored OER's specific impact among those who are presumed to benefit most from that potential: historically underserved student populations (see Arbor 2011;Jenkins et al 2018;Clinton & Khan 2019;Colvard, Watson, & Park 2018;Delgado, Delgado, & Hilton 2019). This is because OER and textbook affordability studies typically control for issues of difference, or else fail to disaggregate their final data altogether.…”
mentioning
confidence: 99%
“…588-89). While much of the OER research published since 2016 has continued to focus on these topics and perspectives (Hilton, 2017;Ikahihifo, Spring, Rosecrans & Watson, 2017;Brandle, 2018;Colvard, Watson, & Park, 2018;Delgado, Delgado, & Hilton, 2019), in the last 5-to-10 years there has also been a noticeable increase in publications by academic librarians about their OER support and leadership.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies on OER reported their significant impact on education, improving its quality and efficiency in providing the educational resources to students, and economy that makes OER the preferable option for many educational institutions (Delgado, Delgado, Hilton, 2019;Vojtech and Grissett, 2017;Mosharraf and Taghiyareh, 2016). Globally, Baas, Admiraal, and van den Berg (2019) argued that OER have full capacity to cause positive change to higher education.…”
Section: Literature Reviewmentioning
confidence: 99%